THE STUDENTS “ERRORS IN PRONUNCIATION OF THEENGLISH CONSONANTS AT THE ELEVENTH GRADE OF SMA SWASTA ERLANGGA PEMATANGSIANTAR - Natanael Saragih; Kormika Marpaung (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
The purpose of this research is to find out the students’ Errors in Pronunciation the English Consonants at class XI grade of SMA Swasta Erlangga Pematangsiantar. This research was conducted at SMA Swasta Erlangga Pematangsiantar. The researcher used qualitative approach with content analysis method. Then, population in this research is the eleventh grade students of SMA Swasta Pematangsiantar that consisted of 2 classrooms which consists of 30 students. The result of this research was the researcher’s found the students’ Errors in Pronunciation of the English consonants namely: The english consonants /d/, /t∫/, /j/, /t/, /s/, /ƞ/, /l/, and /r/. The English consonants errors /d/ is 60 (15,38%), /t∫/ is 50 (12,82%), /j/ is 52 (13,33%), /t/ is 92 (23,58%), /s/ is 47 (12,05%), /ƞ/ is 45 (11,53%), /l/ is 39 (10%), and /r/ is 5 (1,28%). Based on the data analysis that the dominant errors in pronunciation the English consonants is /t/ 92 (23,58%), it could be happen because the students did not read seriously, they have little desire to learn English, they don’t have confidence, they get bored easily, and the students are afraid to be wrong